The UFair Questionnaire: Measuring Perceived University Unfairness and Its Association with Students’ Mental Health - Herr, Raphael; Deyerl, Veronika; Diehl, Katharina (Behavioral Sciences, 2025)
University students face various stressors that may jeopardize their mental health. The aim of this study was to adapt the concept of organizational justice to universities, develop and validate a corresponding questionnaire (UFair: University Fairness Questionnaire) in German, and estimate its association with mental health. Perceived university unfairness was measured in 1105 students using the newly developed 20-item UFair Questionnaire. Mental health was assessed using the Patient Health Questionnaire (PHQ-8, depression) and the Maslach Burnout Inventory for Students (MBI-SS, burnout). The UFair Questionnaire had good psychometric properties, a unidimensional factor structure, and a considerable association with the mental health indicators. Perceived injustice also represents a stressor in the university setting, showing a considerable relation with students’ mental health. The relevance of these aspects to the health of students should be recognized and considered by universities. Valid measurement using the UFair Questionnaire represents the basis for possible preventive approaches and interventions.
CRIS-Team Scopus Importer:2025-10-10
Keywords: Germany; injustice; mental health; organizational justice; questionnaire; stress; students; unfairness; university; validation